Case Report: Renal potassium wasting in SARS-CoV-2 infection - Mabillard, Holly (F1000Res, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with many potentially fatal complications. Renal involvement in various forms is common in addition to serum electrolyte disturbances. Early reports suggest that hypokalaemia may frequent those with SARS-CoV-2 infection and various aetiological factors may cause this electrolyte disturbance. A Chinese retrospective study has demonstrated renal potassium wasting in patients infected with SARS-CoV-2, however, it is not known if these patients were receiving diuretic therapy which may be a contributing factor. This case report illustrates an example of renal potassium wasting in SARS-CoV-2 infection in the absence of diuretics and extra-renal mechanisms with important lessons learned.